Strategi Penyelesaian Konflik Hubungan Industrial Pada PT PLN (Persero) Unit Induk Transmisi Jawa Bagian Timur Dan Bali Dalam Meningkatkan Kinerja Karyawan - Siska Satria Ningsih; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract In a company, there is an industrial relationship that is mutually agreed upon between the company and its employees in an agreement. The agreement regulates the rights and obligations of the parties in order to create a harmonious industrial relationship. In this case, sometimes an internal conflict arises within the company which results in hampered productivity. Therefore, researchers want to know how industrial relations occur and strategies for resolving industrial relations conflicts at PT PLN (Persero) Unit Induk Transmisi Jawa Bagian Timur dan Bali (UIT JBM). So that this research is entitled